Para/inquiry : postmodern religion and culture - Taylor, Victor E. (Routledge, 2000)
Para/Inquiry represents the next generation of postmodern studies. It is interdisciplinary in focus with attachments to religion, cultural studies and literature. It provides a fresh look at the history and main themes of postmodernism.